PEMANFAATAN KATALIS Ca3(PO4)2 DARI TULANG IKAN TUNA PADA PEMBUATAN BIODIESEL DARI MINYAK BINTANGGUR (Callophyllum inophyllum L) - Rosmawaty Rosmawaty; I Wayan Sutapa; Desy Kamanasa (Molluca Journal of Chemistry Education (MJoCE), 2018)
Biodiesel synthesis from bintanggur oil (Callophyllum inophyllum L.) has been done through esterification and transesterification process with Ca3(PO4)2 catalyst and methanol solvent. Production of Ca3(PO4)2 catalyst process was conducted by calcination of the Tuna’s bone at 1000ºC for 2 hours. The catalyst result was got 58.75% and then been characterized with XRD. The esterification process was performed with methanol and bintanggur oil in molar ration of 1:9 for 2 hours with 1.25% H2SO4. The transesterification process was conducted with bintanggur oil and methanol in molar ratio of 1:12 for 9 hours with 10% Ca3(PO4)2 catalyst. The conversion result by 1H-NMR is 73.76% and experimentally was 56.87%. Biodiesel was analyzed with FTIR, GC-MS, 1H-NMR and ASTM. ASTM testing result show there are spesific density of 0.9204 g/cm3, kinematic viscosity of 29.68 mm2/s, flash point at 188.5ºC, pour point at 6ºC, Conradson carbon residue of 0.162%, water content 0.175%, and copper strip corrosion of 1b